Development and validation of the Executive Functioning Scale - Uljarević, Mirko; Cai, Ru Ying; Hardan, Antonio Y.; Frazier, Thomas W. (Frontiers in Psychiatry, 2023)
Executive functioning (EF) processes are essential for adaptive and flexible responding to the demands and complexities of everyday life. Conversely, if impaired, these processes are a key transdiagnostic risk factor that cuts across autism and a range of other neurodevelopmental (NDD) and neuropsychiatric (NPD) conditions. However, there are currently no freely available informant-report measures that comprehensively characterize non-affective (e.g., working memory, response inhibition, and set shifting) and affective (e.g., emotion regulation) EF subdomains. This study describes the development, refinement, and initial psychometric evaluation of a new 52-item Executive Functioning Scale (EFS). Two independent data collections yielded exploratory (n= 2004, 169 with autism, ages 2–17) and confirmatory (n= 954, 74 with autism, ages 2–17) data. Exploratory Structural Equation Modelling (ESEM) model with six specific factors that closely matched hypothesized executive functioning subdomains of working memory and sequencing, response inhibition, set-shifting, processing speed, emotion regulation, and risk avoidance, and one general factor, showed the best fit to the data and invariance across age, sex, race, and ethnicity groups. Model reliability and internal consistency were excellent for the general factor (ω=.98; α=.97) and specific factors (ω≥.89-.96; α≥.84-.94). Conditional reliability estimates indicated excellent reliability (≥.90) for the total EF scale and adequate or better reliability (≥.70) for subscale scores. With further replication, the EFS has excellent potential for wide adoption across research and clinical contexts.